Microemulsion-based synergistic dual-drug codelivery system for enhanced apoptosis of tumor cells - Qu, Ding (Int J Nanomedicine, 2015)
A microemulsion-based synergistic dual-drug codelivery system was developed for enhanced cell apoptosis by transporting coix seed oil and etoposide into A549 (human lung carcinoma) cells simultaneously. Results obtained by dynamic light scattering showed that an etoposide (VP16)-loaded coix seed oil microemulsion (EC-ME) delivery system had a small size around 35 nm, a narrow polydispersity index, and a slightly negative surface charge. The encapsulating efficiency and total drug loading rate were 97.01% and 45.48%, respectively, by high-performance liquid chromatography. The release profiles at various pH values showed an obvious pH-responsive difference, with the accumulated amount of VP16 released at pH 4.5 (and pH 5.5) being 2.7-fold higher relative to that at pH 7.4. Morphologic alteration (particle swelling) associated with a mildly acidic pH environment was found on transmission electron microscopy. In the cell study, the EC-ME system showed a significantly greater antiproliferative effect toward A549 cells in comparison with free VP16 and the mixture of VP16 and coix seed oil. The half-maximal inhibitory concentration of the EC-ME system was 3.9-fold and 10.4-fold lower relative to that of free VP16 and a mixture of VP16 and coix seed oil, respectively. Moreover, fluorescein isothiocyanate and VP16 (the green fluorescent probe and entrapped drug, respectively) were efficiently internalized into the cells by means of coix seed oil microemulsion through intuitive observation and quantitative measurement. Importantly, an EC-ME system containing 20 μg/mL of VP16 showed a 3.3-fold and 3.5-fold improvement in induction of cell apoptosis compared with the VP-16-loaded microemulsion and free VP16, respectively. The EC-ME combination strategy holds promise as an efficient drug delivery system for induction of apoptosis and treatment of lung cancer.